The Pósa method with ATD lenses: Praxeological analysis on math problems in Hungarian talent care education with ‘recursion’ in their logos blocks La méthode Pósa avec des lentilles TAD: analyse praxéologique des problèmes mathématiques dans l’enseignement hongrois de soins aux talents avec «récursion» dans leurs blocs de logos - Katona, Dániel (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2020)
Abstract. The praxeological analysis of selected questions used in the Hungarian Pósa method is presented, focusing on a common element in their logos blocks, called recursive thinking. As part of a broader research with reverse didactic engineering methodology, aiming at theorizing the ‘intuitively’ developed Pósa method, the present findings are also compared to previous results and re-interpret the concepts of kernel and web of problem thread. Based on these results gained by using tools of the Anthropological Theory of the Didactic, the paper offers a partial description of the didactic strategy of the Pósa method for inquiry-based learning mathematics and raises questions for further research. Résumé Nous présentons l’analyse praxéologique de certaines questions utilisées dans la méthode hongroise Pósa, en nous concentrant sur un élément commun à leurs logos blocs, appelé pensée récursive. Dans le cadre d’une recherche plus large qui met en place une méthodologie d’ingénierie didactique inverse visant à théoriser la méthode de Pósa développée "intuitivement", les résultats actuels réinterprètent les concepts de noyau et de réseau de fils de problèmes. Sur la base des résultats obtenus en utilisant les outils de la théorie anthropologique du didactique, l’article offre une description partielle de la stratégie didactique de la méthode Pósa pour l’apprentissage des mathématiques basé sur l’enquête, et soulève des questions pour des recherches ultérieures.